A training program to improve neuromuscular indices in female high school volleyball players - Noyes, F. R.; Barber-Westin, S. D.; Smith, S. T.; Campbell, T. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to determine if a sports-specific training program could improve neuromuscular indices in female high school volleyball players. We combined components from a previously published knee ligament injury prevention intervention program for jump and strength training with additional exercises and drills to improve speed, agility, overall strength, and aerobic conditioning. We hypothesized that this sports-specific training program would lead to significant improvements in neuromuscular indices in high school female volleyball players. Thirty-four athletes (age 14.5 years ± 1.0) participated in the supervised 6-week program, 3 d/wk for approximately 90-120 minutes per session. The program was conducted on the school's volleyball court and weight room facilities. The athletes underwent a video drop-jump test, multistage fitness test, vertical jump test, and sit-up test before and after training. A significant increase was found in the mean VO2max score (p < 0.001), where 73% of the athletes improved this score. A significant improvement was found in the sit-up test (p = 0.03) and in the vertical jump test (p = 0.05), where 68% of the athletes increased their scores. In the drop-jump video test, significant increases were found in both the mean absolute knee separation distance (p = 0.002) and in the mean normalized knee separation distance (p = 0.04), indicating improved lower limb alignment on landing. No athlete sustained an injury or developed an overuse syndrome during training. This program significantly improved lower limb alignment on a drop-jump test, abdominal strength, estimated maximal aerobic power, and vertical jump height and may be implemented in high school female volleyball programs.